Pemberdayaan Masyarakat melalui Program Desa Tangguh Bencana (DESTANA) Sebagai Upaya Mitigasi Banjir Rob di Kabupaten Cirebon - Ananda Diah Oktaviani; Febby Amanda Putri; Niken Tunjung Murti Pratiwi; Iriani Setyaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The coastal area is the border area between land and sea. Coastal areas have an important role in maintaining that seawater does not enter the mainland. Poor coastal conditions will disturb the stability of the environment around the coast. Natural disasters such as tidal floods are the focus of attention for coastal communities, especially in Cirebon District. The purpose of this community service program is to reduce the risk of tidal flooding through disaster mitigation efforts. The dedication was carried out in July 2019 with the method of socialization and brainstorming. Socialization and brainstorming were attended by villagers. The results show that the community is very enthusiastic about this program, this is evidenced by the formation of working groups (LWGs) who are fully responsible for all pre-disaster activities, during disasters and after disasters. The program that has been carried out by LWG is participating in socialization related to DESTANA and making disaster mitigation maps and following coastal cleanup activities. Keywords: tidal flooding, disaster mitigation, empowerment